Youth and Ethical Crises in the Age of the Internet: Causes, Impacts, and Solutions - Nawaz, Zunaira; Bibi, Sumaira; Sehar, Rameesha (Journal of Islamic and Religious Studies, 2025)
This article discusses the moral challenges facing the younger generation. In today’s era of the Internet, young people are encountering numerous moral issues, leading to the deterioration of their character and the weakening of high moral qualities such as truthfulness, shame, and modesty. One of the major causes of these moral problems is excessive leisure time. This article explores the root causes of this issue and suggests effective ways to manage and utilize time productively. Another critical issue severely affecting today's youth is the easy access to pornographic material. This article examines why such content has become so readily available to young people, highlights the underlying reasons, and presents a comprehensive solution to overcome this challenge. Additionally, the negative impact of bad company is discussed, along with its remedy based on Islamic teachings. Another important issue discussed in detail in the article is the misconceptions about Islam. The underlying reasons for the youth’s growing doubts about Islam are examined, and a comprehensive solution is presented in the light of the Qur’an to help reform their moral inclinations. All the solutions mentioned in this article are derived from authentic religious sources and can be instrumental in the moral growth of the youth. By following these guidelines, young people can not only strengthen their bond with Allah Almighty but also protect themselves from the harmful influences of social media.